DESIGN AND PERFORMANCE ANALYSIS OF A MULTILEVEL INVERTER USING A BIPOLAR PWM SWITCHING SCHEME - Muhammad Essa Majeed; Jalil Akbarzai; Muhammad Qasim; Abdul Rahmaan Khan; Faheem Ali; Muhammad Amir (Spectrum of Engineering Sciences, 2025)
This paper focuses on the design and simulation of a single-phase PWM multi-level inverter using the bipolar switching scheme to improve efficiency and quality with the help of pulse width modulation (PWM) for DC to AC voltage converters. This research emphasizes on obtaining well defined output voltage, reduction of total harmonic distortion (THD), and enhancing energy conversion effectively and efficiently by utilizing multilevel inverter and phase disposition (PD) modulation techniques. The inverter shows outstanding results, achieving an efficiency of 96% and producing an output voltage of 110-Volts at 60 Hz from the 80-Volt DC input from each bridge. In this particular simulation in MATLAB, the inverter demonstrates a significant reduction in THD, with an output voltage THD of 1.36% and a current THD of 0.13%. Our approach is effective and has the potential to produce stable AC output even with RL loads and maintain high power quality. The paper highlights the significance of modulation techniques in increasing the performance of inverters and also underscores the importance of selecting suitable methods for different applications to ensure the best performance and efficiency.